2019
DOI: 10.1002/ptr.6260
|View full text |Cite
|
Sign up to set email alerts
|

Pheophorbide A from Gelidium amansii improves postprandial hyperglycemia in diabetic mice through α‐glucosidase inhibition

Abstract: This study was designed to determine the inhibitory effects of pheophorbide A on carbohydrate digesting enzymes and its ability to improve postprandial hyperglycemia in streptozotocin (STZ)‐induced diabetic mice. Pheophorbide A caused noticeable inhibitory effects on α‐glucosidase and α‐amylase, with half‐maximal inhibitory concentrations (IC50) of 80.65 ± 5.90 and 76.48 ± 6.31 μM, respectively. The pheophorbide‐mediated inhibition of α‐glucosidase and α‐amylase was significantly more effective than that of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
2
5
1
Order By: Relevance
“…In contrast to our in-silico data, Kim et al. ( 15 ) showed that 2 g/kg body weight of pheophorbide A was administered to 4‐week‐old male ICR mice and was found to be non-toxic. Another report suggests that maximum permissible amount of pheophorbide A was determined at 1,000 mg/g and a recommended dosage of 25 mg/day ( 43 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our in-silico data, Kim et al. ( 15 ) showed that 2 g/kg body weight of pheophorbide A was administered to 4‐week‐old male ICR mice and was found to be non-toxic. Another report suggests that maximum permissible amount of pheophorbide A was determined at 1,000 mg/g and a recommended dosage of 25 mg/day ( 43 ).…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, polyherbal formulation MA, a complex concoction of bioactive compounds, was considered, which showed various lead phytocompounds. Our previous study reported pheophorbide A in the major peak of LC-MS/MS of MA ( 12 ) similar to other supporting studies in the literature with regard to DM management ( 14 , 15 ). These studies suggest that pheophorbide A manages DM by enhancing insulin secretion.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The best activity (75.41±0.03%) was obtained at 0.5 mg/mL against α-glucosidase. This is in support of results reported by Kim et al (2019) that pheophorbide A, an unesterified analog isolated from Gelidium amansii caused significant decrease in the activity of α-glucosidase and α-amylase when compared to Acarbose 40 . Palmitic acid showed the best α-glucosidase activity in all the concentrations tested ranging from 324.69-355.89 µM.…”
Section: Discussionsupporting
confidence: 92%
“…Pheophorbides are commonly produced by most photosynthetic plants and microalgae as breakdown products of chlorophyll upon senescence and/or fruit ripening [17]. Pheophorbide a (PA) exerts antiviral [18], antioxidant [19], anti-inflammatory [20], antidiabetic [21,22], anticancer [23], and antiparasitic effects [24] through regulation of hepatitis C virus, scavenging of the 2,2-diphenyl-1-picryldrazyl-radical, and induction of tumor necrosis factor alpha (TNFα) secretion, α-glucosidase activity, insulin secretion, cancer cell proliferation, and Leishmania amazonensis cell death, respectively. PA is a good photosensitizer and strongly absorbs light energy at 650−700 nm [25].…”
Section: Introductionmentioning
confidence: 99%